Support staff liaising effectively with professionals for the rational use of psychotropics for behaviours that challenge in adults with intellectual disabilities: Findings from a co-design event - Limbu, Bharati; Deb, Shoumitro Shoumi (Frontiers in Psychiatry, 2022)
Experience Based Co-Design (EBCD) and co-production are interdisciplinary collaborative approaches to improve health care services by involving all stakeholders. These approaches capture the experiences of all stakeholders who come in contact with services and use experiences as evidence to promote and implement service changes. The use of psychotropic medications for behaviours that challenge (BtC) in people with intellectual disabilities (ID) is a complex issue because of its off-license use and use in combination with other medications for physical and psychiatric co-morbidities, which leads to overmedication of people with ID. As support staff play a pivotal role in the prescribing for people with ID, we have developed a staff training programme, SPECTROM, to help reduce overmedication. A project team developed SPECTROM under the guidance of a Programme Development Group (PDG) consisting of 21 stakeholders. The PDG analysed data from a literature review, four focus groups and a co-design event day involving 26 stakeholders. In this paper, we have presented data based on the findings from the co-design event day, primarily on the issue of support staff effectively liaising with professionals such as doctors, nurses and other community learning disability team members. In-depth information and recommendations were proposed at the co-design event, which helped develop the draft SPECTROM. The draft was finalised after receiving feedback from 56 stakeholders. Co-production and a modified EBCD can be successfully used to create training interventions and improve health care services. More research should utilise co-production and EBCD and use service users’ experiences to develop interventions and improve health care services.